'Twists and turns': the strategic manipulation of ISIS, the caliphate, and political branding - Oztig, Lacin Idil (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
ISIS's declaration of a caliphate in 2014 sent shockwaves around the world. What objectives did ISIS leaders seek to achieve through their audacious attempt to resurrect such an archaic institution? This study scrutinises Dabiq, the official transnational media outlet of ISIS published between 2014 and 2016, from the perspective of political marketing. It primarily argues that ISIS not only sells 'a story' but also 'a brand' in its pursuit of global influence and power. A close reading of Dabiq reveals that the organisation strips the concept of the caliphate of its rich historical context and diverse interpretations and turns it into a 'political brand' specifically tailored to further its political ambitions. In the magazine, while the caliphate is associated with the glorious age of Muslims, there is a deliberate attempt to obscure the existence of weak caliphal regimes, the caliphal titles used by Shia Muslims (under Fatimid rule), or the caliphal periods during which religious tolerance and generosity were exhibited toward non-Muslims. This caliphal brand is marketed through a highly simplified and distorted characterisation of history, coupled with selective interpretations of hadiths and Qur'anic verses, as well as disturbing violent imaginary. This branding technique is used to outmanoeuvre the organisation's competitors in the radical Islamist market by presenting an appealing image that showcases the organisation' readiness and ability to unite all Sunni Muslims under a singular banner. By evoking themes of 'unity', 'power', and 'action', the caliphal brand is crafted to appear attractive to its target audience-Sunni Muslims-by manipulating the most fundamental human desires: the need for belonging, certainty and empowerment.
Keywords: SOCIAL MEDIA; STATE; International Relations; Government & Law